Clinical characteristics and early identification of augmented renal clearance in PICU patients with severe sepsis associated with MRSA infection - Wang, Haonan; Li, Jiaqing; Li, Xian; Li, Han; He, Yinglang; Tan, Rui; Mei, Xuejian; Zha, Haoyu; Fan, Mingxing; Peng, Shuangshuang; Hou, Nan; Li, Zhe; et al. (Frontiers in Pediatrics, 2024)
To investigate the epidemiological characteristics of Augmented Renal Clearance (ARC) in severe sepsis children with MRSA infection and find risk factors to establish a model predicting ARC onset in PICU.Retrospective study, in which ARC was defined by estimated glomerular filtration rate (eGFR) measured by the modified Schwartz formula above 130 mL/min/1.73m 2 . Univariable and multivariable logistic regression analyses were performed to find the predictor for ARC. Multistrategy modeling was used to form an early prediction model for ARC, which was evaluated by the area under the ROC curve (AUC), accuracy (ACC) and other indicators.One China PICU.